High‐Capacity and Stable Li‐O2 Batteries Enabled by a Trifunctional Soluble Redox Mediator - Xiong, Qi; Huang, Gang; Zhang, Xin‐Bo (Angewandte Chemie International Edition, 2020)
Li‐O2 batteries with ultrahigh theoretical energy densities usually suffer from low practical discharge capacities and inferior cycling stability owing to the cathode passivation caused by insulating discharge products and by‐products. Here, a trifunctional ether‐based redox mediator, 2,5‐di‐tert‐butyl‐1,4‐dimethoxybenzene (DBDMB), is introduced into the electrolyte to capture reactive O2− and alleviate the rigorous oxidative environment of Li‐O2 batteries. Thanks to the strong solvation effect of DBDMB towards Li+ and O2−, it not only reduces the formation of by‐products (a high Li2O2 yield of 96.6 %), but also promotes the solution growth of large‐sized Li2O2 particles, avoiding the passivation of cathode as well as enabling a large discharge capacity. Moreover, DBDMB makes the oxidization of Li2O2 and the decomposition of main by‐products (Li2CO3 and LiOH) proceed in a highly effective manner, prolonging the stability of Li‐O2 batteries (243 cycles at 1000 mAh g−1 and 1000 mA g−1). A trifunctional ether‐based redox mediator, DBDMB, is introduced into the electrolyte to capture reactive discharge intermediates (O2−) with reduced formation of by‐products, regulate solution growth of Li2O2, and co‐oxidize Li2O2 and by‐products (Li2CO3 and LiOH). Li‐O2 batteries with large capacity and long cycling stability have been achieved.